Branneria bonoculus, n. sp., a second species in the North American milliped family Branneriidae (Diplopoda: Chordeumatida: Brannerioidea) - Shear, William A. (Zootaxa, 2003)
Branneria bonoculus, n. sp., is described from southwestern Arkansas (USA) as the second species in its genus and family. Some misinterpretations of branneriid gonopods are corrected, and the composition of the superfamily Brannerioidea is briefly discussed. New figures of the gonopods of Branneria carinata (Bollman) are presented.